2016
DOI: 10.1186/s12876-016-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological regimens for eradication of Helicobacter pylori: an overview of systematic reviews and network meta-analysis

Abstract: BackgroundApproximately half of the world’s population is infected with Helicobacter pylori (H.pylori), a bacterium shown to be linked with a series of gastrointestinal diseases. A growing number of systematic reviews (SRs) have been published comparing the effectiveness of different treatments for H.pylori infection but have not reached a consistent conclusion. The objective of this study is to provide an overview of SRs of pharmacological therapies for the eradication of H.pylori.MethodsMajor electronic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
1
30
0
2
Order By: Relevance
“…The eradication rate (96.9%, ITT analysis) obtained by treatment with Pylera® in the present series of patients from Southern Italy was higher than that reported by previous international studies [12,51,55], but similar to that reported by another recent Italian study both in patients on first treatment and in rescue therapy [56], confirming the elevated therapeutic efficacy of regimen with bismuth subcitrate potassium in this specific geographical area.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The eradication rate (96.9%, ITT analysis) obtained by treatment with Pylera® in the present series of patients from Southern Italy was higher than that reported by previous international studies [12,51,55], but similar to that reported by another recent Italian study both in patients on first treatment and in rescue therapy [56], confirming the elevated therapeutic efficacy of regimen with bismuth subcitrate potassium in this specific geographical area.…”
Section: Discussionsupporting
confidence: 86%
“…Alternative second-line (i.e. when first-line therapy fails) therapeutic approaches contain PPI plus amoxicillin plus levofloxacin [12]. More recently, a combination of tetracycline hydrochloride, metronidazole, and bismuth subcitrate potassium (Pylera®) has been developed as either the first-and second-line regimen [5,8,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was thus considered possible for us to compare vonoprazan-based therapy with PPI-based therapy after eliminating CAM-resistant organism ratios on H. pylori eradication therapy. Xin et al [39] performed a meta-analysis of H. pylori eradication therapies using 5 PPIs and ranked PPIs in the order of effects. The top 2 PPIs were the second-generation PPIs EPZ and RPZ, which indicated that second-generation PPIs are more effective than first-generation PPIs in H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The AMSTAR tool has been used previously in > 170 methodological quality-assessment articles in other fields of research, including cardiology, 28,29 gastroenterology, 30 gynaecology, [31][32][33][34] neumology, 35,36 neurology, 37-39 neurosurgery, [40][41][42] general surgery, 43,44 urology, 45,46 radiology 47 and odontology. 48 Most studies achieved similar general conclusions to our study.…”
Section: Discussionmentioning
confidence: 99%